Evaluation of Acalypha indica Aerial Part Ethanol Extract for Anticancer Activity in MDA-MB-231 Cells Supported by GC-MS Chemical Fingerprinting - Ancy, Rajadurai; Parimala, Selva Mabel (Asian Journal of Biological and Life Sciences)
Background: Plant extracts, their parts, and active chemicals are used for many decades in cancer management. Aim: In this study, the aerial part (stems, leaves and flowers) of Acalypha indica (Family: Euphorbiaceae) was cold-extracted using ethanol solvent, and the anticancer activity was assessed using breast cancer cell line, MDA-MB-231. Materials and Methods: The work investigated the cytotoxic effect of Acalypha indica using various cytological methods like MTT assay, DNA ladder assay, AO/EB dual staining method and Mitochondrial Membrane Potential (MMP) assay in different extract concentrations ranging from 20 to 100 μg/mL. GC-MS analysis was performed to identify the compounds. Results: Changes in the shape and appearance of both untreated and extract-treated cells were viewed under a digital inverted microscope after 24 hr and recorded as images. The ethanol extract of A. indica showed toxic effects on cancer cells, reducing their survival in a dose-dependent way. IC50 value was calculated as 59.97 μg/ mL. DNA ladder assay suggests extensive cytogenetic damage in the extract-treated cells. The AO/EB assay and MMP assay results show apoptosis of varying degrees in the extract-treated cells. 60 plant compounds were identified by GC-MS analysis. Conclusion: Thus, this preliminary study indicates that the ethanol-extracted Acalypha indica aerial parts can be used to treat breast cancer. Further pharmacological activities and phytochemical study is required to confirm its potential.
Keywords: AO/EB staining; Carcinoma; Medicinal plant; MTT; Phytochemicals